Effectiveness in vitro of ethanolic extract from chrysanthemum and acaropathogen fungi in controlling the red palm mite (Bioagro, 2018)
Red palm mite, Raoiella indica, is considered an economic important pest in coconut plants (Cocos nucifera L.); however, information about ecologically sustainable strategies of control is still scarce. In this study, in vitro effectiveness of ethanolic extract (EE) of pyrethrum (Chrysanthemum cinerariifolium) and compatibility with acaropathogenic fungi (Isaria fumosorosea and Beauveria bassiana) on R. indica control were evaluated. In the laboratory, mites were reared in rearing units using coconut leaf discs cv. Malayan Yellow Dwarf. Mortality of eggs, larva and adult mite by single and combined application of EE (0.25, 0.50, 1.0, 1.5, 2.5, 5, 10 and 15 %) and fungus species was demonstrated. Although the EE at 0.25 and 0.5 % inhibited the mycelial growth of I. fumosorosea and B. bassiana, conidial production was also promoted in both fungi species. Single or combined use of treatments did not show differences in egg, larvae or adult mite’s mortality; however, the EE seems to provoke a slightly higher effect on the mite.
Keywords: Coconut; Raoiella indica; sustainable management